LEARNING STRATEGIES USED BY STUDENTS IN ACQUIRING FLUENCY IN FOREIGN LANGUAGE - Kartini Mirsah; Abd. Muin (UIN Alauddin Makassar, 2014)
ABSTRACTThis research aims to find out kinds of learning strategies dominantly used by the students of English and Literature Department of UIN Alauddin Makassar under cumlaude (3.76-4.00) GPA. This research is important to know, especially for the students in foreign language major, because learning strategies has function as the way to improve language achievement and students ability in applying foreign language. The researcher uses a descriptive method in analyzing the data. The researcher states the result of data analysis by describing them through percentage and explanation. The researcher uses questionnaire as the instrument to collect the data. Referring to the finding and discussion of this research, the result shows that from three kinds of learning strategies: 1. Metacognitive learning strategies, 2. Cognitive learning strategies, 3. Socioaffective learning strategies proposed by O’Malley et al, the highest learning strategies used by the students of English and Literature Department of Adab and Humanities Faculty of UIN Alauddin Makassar who have cumlaude (3.76-4.00) GPA is socioaffective learning strategies, the second is cognitive learning strategies, and the last is metacognitive learning strategies. So, the writer concludes that learning strategies that dominantly used by students of English and Literature Department of Adab and Humanities Faculty of UIN Alauddin Makassar who have cumlaude (3.76-4.00) GPA is socioaffective learning strategies.